HINDU YOUTH CREATES PEACE IN THE MILLENNIAL ERA - Ni Made Indiani; I Made Santosa (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2019)
Nowdays, in the millennial era, which is called the digital age, people should get to know 3 (three) important things, namely, data literacy, technology literacy, and human resource literacy. The purpose of this paper is to discuss how young Hindus can master these three things, utilize data accurately and can talk, discuss and disseminate information based on available data so that they are not underestimated by other religions. Similarly, the use of technology in an appropriate manner by their needs, so they can compete in the world of work. By using the four pillars of education concepts, namely, 1) learning to know, (2) learning to do, (3) learning to be, and (4) learning to live together, then Hindu resources will be able to compete in healthily and harmoniously way side by side with other nations, who have different customs and religions. This thought is important to spread because it needs to be realized by young Hindus to be able to create world peace. Thus a true peace begins with individuals, families, and communities. No hoax, no violence.